A facile route to fluoroalkylsiloxane polymers having resistance to corrosive acidic conditions: Synthesis and characterization. (December 2017) - Indulekha, K.; Mathew, Ann; Rajeev, R.S.; Ninan, K.N.; Gouri, C.
Graphical abstract: Highlights: Room temperature curable fluoroalkylsiloxane is synthesized and characterized. The polymer exhibits excellent hydrophobicity and lipophobicity. It offers superior resistance to acidic and oxidative media like conc. HF and HNO3 . The polymer can act as both adhesive and coating as proved by the LSS evaluations. Abstract: Polysiloxanes having 3, 3, 3-trifluoropropyl (TFP) groups attached to the silicon atom are highly attractive by virtue of their unique properties such as extreme solvent resistance and broad service temperatures. Though fluoroalkylsiloxane polymers are known for their resistance to hydrocarbon solvents and oils, reports on room temperature curable fluoroalkylsiloxane polymer based coatings that are resistant to corrosive acidic and oxidative environments are very rare. In this paper, for the first time, we report the synthesis of vinyl terminated fluorosilicone copolymer, poly(methyltrifluoropropyl- co -methylvinyl) siloxane (V-PFMVS) with very high TFP content (77 mol%) and 23 mol% vinyl content, and its comparison of properties with non-fluorinated counterpart, vinyl terminated poly(dimethyl- co -methylvinyl) siloxane (V-PDMVS). The synthesised copolymers were obtained in high yields of 70–75% with number average molecular weight (Mn ) of 65, 000 and were cured using cyclic hydridosiloxane via hydrosilylation route. Cured V-PFMVS exhibited increased hydrophobicity compared to cured V-PDMVS (contact angle 113° vs . 91°). The corresponding silica reinforced composites also were processed and evaluated for dynamic mechanical and thermal properties as well as response to various environments including hexane, conc. HNO3 and HF. Swelling studies proved the role of -CH2 CH2 CF3 groups in imparting excellent resistance to hexane and better resistance to corrosive acidic environments as illustrated by the low weight loss after exposure to conc. HNO3 and HF in the case of V-PFMVS/composite. Lap shear strength (LSS) evaluation on aluminium substrate proved its capability as a promising adhesive. The superior properties of the V-PFMVS/composite are correlated to its chemical composition.